Pengaruh Kecerdasan Emosional dan Organizational Citizhensip Behavior Terhadap Kinerja Tenaga Kesehatan pada Puskesmas Bola Kabupaten Sikka - Donbosko Pehan Waton; Antonius Philippus Kurniawan; Viktor Eko Transilvanus (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
The background of this research is health workers’ performance at Bola Health Center in Sikka Regency was not optimal. This study aimed to (1) describe health workers performance, emotional intelligence, and organizational citizenship behavior. (2) analyzing chiter partailly or simultaneously the influence of emotional intelligence and organizational citizenship behavior on the work performance of health workers at Bola Health Center Sikka Regency. The population in this study were health workers at Bola Health Center in Sikka Regency, totaling 64 people. This research was conducted through census or saturated sampling due limited population. Data were collected through questionnaires and analyzed using descriptive methods and inferential statistics, namely multiple linear regression. Hy pothesis testing in done through the t test and and F test. The results of the descriptive analysis revealed that the performance variabels of health workers, emotionaal intelligence, and organizational citizenship behavior were categorized as good. The results of the t-test statistics showed that partially the variabels of emotional intelligence and organizational citizenship behavior had a positive and significant influence on health workers performance. The statisticial results of the F test showed that simultancously the variables of emotional intelligence and organizational citizenship behavior had a significant influence on health workers performance. The results of the determination analysis showed that the contribution of emotional intelligence and organizational citizenship behavior on health workers performance in Bola Health Center wa 21,3%.